c-Myc Drives inflammation of the maternal-fetal interface, and neonatal lung remodeling induced by intra-amniotic inflammation - Tan, April W.; Tong, Xiaoying; Alvarez-Cubela, Silvia; Chen, Pingping; Santana, Aline Guimarães; Morales, Alejo A.; Tian, Runxia; Infante, Rae; Nunes de Paiva, Vanessa; Kulandavelu, Shathiyah; Benny, Merline; Dominguez-Bendala, Juan; et al. (Frontiers in Cell and Developmental Biology, 2024)
Background: Intra-amniotic inflammation (IAI) is associated with increased risk of preterm birth and bronchopulmonary dysplasia (BPD), but the mechanisms by which IAI leads to preterm birth and BPD are poorly understood, and there are no effective therapies for preterm birth and BPD. The transcription factor c-Myc regulates various biological processes like cell growth, apoptosis, and inflammation. We hypothesized that c-Myc modulates inflammation at the maternal-fetal interface, and neonatal lung remodeling. The objectives of our study were (1) to determine the kinetics of c-Myc in the placenta, fetal membranes and neonatal lungs exposed to IAI, and (2) to determine the role of c-Myc in modulating inflammation at the maternal-fetal interface, and neonatal lung remodeling induced by IAI. Methods: Pregnant Sprague-Dawley rats were randomized into three groups: 1) Intra-amniotic saline injections only (control), 2) Intra-amniotic lipopolysaccharide (LPS) injections only, and 3) Intra-amniotic LPS injections with c-Myc inhibitor 10058-F4. c-Myc expression, markers of inflammation, angiogenesis, immunohistochemistry, and transcriptomic analyses were performed on placenta and fetal membranes, and neonatal lungs to determine kinetics of c-Myc expression in response to IAI, and effects of prenatal systemic c-Myc inhibition on lung remodeling at postnatal day 14. Results: c-Myc was upregulated in the placenta, fetal membranes, and neonatal lungs exposed to IAI. IAI caused neutrophil infiltration and neutrophil extracellular trap (NET) formation in the placenta and fetal membranes, and neonatal lung remodeling with pulmonary hypertension consistent with a BPD phenotype. Prenatal inhibition of c-Myc with 10058-F4 in IAI decreased neutrophil infiltration and NET formation, and improved neonatal lung remodeling induced by LPS, with improved alveolarization, increased angiogenesis, and decreased pulmonary vascular remodeling. Discussion: In a rat model of IAI, c-Myc regulates neutrophil recruitment and NET formation in the placenta and fetal membranes. c-Myc also participates in neonatal lung remodeling induced by IAI. Further studies are needed to investigate c-Myc as a potential therapeutic target for IAI and IAI-associated BPD.